2014
DOI: 10.1371/journal.pone.0084274
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Cardiovascular Responses in Acclimatized Lowlanders on Prolonged Stay at High Altitude: A Longitudinal Follow Up Study

Abstract: Acute exposure to hypobaric hypoxia at high altitude is reported to cause sympathetic dominance that may contribute to the pathophysiology of high altitude illnesses. The effect of prolonged stay at high altitude on autonomic functions, however, remains to be explored. Thus, the present study aimed at investigating the effect of high altitude on autonomic neural control of cardiovascular responses by monitoring heart rate variability (HRV) during chronic hypobaric hypoxia. Baseline electrocardiography (ECG) da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 96 publications
2
24
0
Order By: Relevance
“…A former study of our research group in the same Antarctic environment already evidenced similar results with elevated catecholamine levels and assumed their association with stated immune alterations ( Feuerecker et al, 2014 ). Furthermore, several other studies in (simulated) high altitude investigated well the impact of hypobaric hypoxia on sympathoadrenal and adrenocortical stress responses and found a positive correlation ( Calbet, 2003 ; Simeoni et al, 2011 ; Dhar et al, 2014 ; Aliyev et al, 2017 ; Woods et al, 2017 ). Woods et al (2017) showed that simulated altitude under normobaric or hypobaric hypoxia (equivalent to 3,375 m) appears to induce similar effects in humans than genuine high altitude.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A former study of our research group in the same Antarctic environment already evidenced similar results with elevated catecholamine levels and assumed their association with stated immune alterations ( Feuerecker et al, 2014 ). Furthermore, several other studies in (simulated) high altitude investigated well the impact of hypobaric hypoxia on sympathoadrenal and adrenocortical stress responses and found a positive correlation ( Calbet, 2003 ; Simeoni et al, 2011 ; Dhar et al, 2014 ; Aliyev et al, 2017 ; Woods et al, 2017 ). Woods et al (2017) showed that simulated altitude under normobaric or hypobaric hypoxia (equivalent to 3,375 m) appears to induce similar effects in humans than genuine high altitude.…”
Section: Discussionmentioning
confidence: 89%
“…However, the question whether normobaric and hypobaric hypoxia elicit the same reactions remains contradictory ( Girard et al, 2012 ; Millet et al, 2012 ; Mounier and Brugniaux, 2012 ). Furthermore, to date, most studies investigated the consequences of acute or intermittent hypoxia ( Xie et al, 2001 ; Calbet, 2003 ; Lusina et al, 2006 ; Sander, 2016 ) but data and knowledge about the effect of prolonged and chronic exposure to hypoxic conditions are rather scarce ( Dhar et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The autonomic nervous system (ANS) plays a major role in regulating cardiovascular function (Aubert et al, 2003). To date, studies have reported ANS responses to hypoxia lasting several minutes (Bobyleva & Glazachev, 2007;Botek et al, 2015), hours (Wille et al, 2012), days (Bhaumik et al, 2013) and months (Dhar et al, 2014). However, there is a paucity of studies reporting effects of hypoxia on ANS using ultra-short, for example 1 min, recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, spectral analysis of HR variability has been used and suggested that parasympathetic withdrawal persists even after 18 months at HA (Dhar et al . ). However, this finding should be interpreted with caution, since parasympathetic indices of HR variability may be influenced at HA by the concomitantly increased sympathetic activity and/or pulmonary ventilation (Chapleau & Sabharwal, ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the limited insight derived from spectral analysis of HR variability supports that the observed withdrawal of parasympathetic activity is at least qualitatively representative for chronic hypoxia (Dhar et al . ). Whether potential changes in autonomic receptor function and/or density affect autonomic regulation of HR at a later point of hypoxic exposure, however, remains to be determined.…”
Section: Discussionmentioning
confidence: 97%